Contested sacred ground and mistaken idioms: pre-reducción and early reducción churches in South-central colonial Peru (AD 1536–1615) - Meddens, Frank M. (2025)
Fil: Meddens, Frank M. University of Reading. School of Archaeology; Reino Unido